Performance of high strength concrete containing Palm Oil Fuel Ash and Metakaolin as Cement Replacement Material - Mohd Hanif, Ismai; Megat Azmi, Megat Johari; Kamar Shah, Ariffin; Putra Jaya, Ramadhansyah; Mohd Haziman, Wan Ibrahim; Yugashini, Yugashini (Hindawi, 2022)
The release of carbon dioxide (CO2) from the cement industry into the atmosphere and the increasing amount of oil palm waste from industrial plants lead to the problem of the greenhouse effect and environmental pollution. Studies on palm fuel ash (POFA) and metakaolin (MK) as a semi-substitute for cement can reduce the problem of the greenhouse effect and environmental pollution, as well as increase and improve the level of strength of concrete. Using mechanical and transport test methods as well as assisted by comparative X-ray Diffraction (XRD) analysis can prove the use of pozzolanic material as a catalyst to the compressive strength of concrete. In this study, slump test, compressive strength test, and water absorption test were conducted on samples containing total cement substitution up to 40% of POFA and MK as cement substitutes. The partial replacement of cement with MK and POFA reduced the workability of the concrete. However, binary and ternary blended concrete containing MK and POFA provide better compressive strength compared to OPC concrete up to 9.5% after 28 days age. Moreover, it was found that, the compressive strength of concrete containing POFA was better than the concrete containing MK up to 4%.